Semantic Field of ‘Wish/Desire’ in the Tatar Language - Shamsutdinov, Rustam; Mukharlyamova, Liliya; Zharkynbekova, Sholpan; Shakirova, Dilyara; Ashrapova, Alsu (Journal of History Culture and Art Research, 2017)
The problems of interdependence of linguocognitive and linguoculturological advanced the cognitive approach in language learning to the forefront. Considering linguistic and extralinguistic knowledge as a comprehensive whole conditioned by correlation between language, thinking, world image, national and cultural peculiarities and human world. In the 21st century each language is like a determining feature of a man, which serves the purposes of communication and is the store of information, accumulated by speech community, as well as fountain of national originality and cultural values. It is the language that is a means of knowing the language speaker, approach to his consciousness, to the discrete units–concepts, national lexemes, language units. One cognizes the linguistic world image and national picture of the world through the linguistic categories. In connection with the above-mentioned, we are interested in analyzing a linguistic category / a concept that expresses the semantic category such as wish/desire in the Tatar language. In the process of studying the linguistic category “wish” and revealing the linguistic means in Tatar, we have found that “wish” acquires a variety of means of linguistic representation – lexically full-value units, syntactic word-combinations, morphological categories and others. For that reason, a diversity of means allowed of our believing that the representation of the structure of linguistic category “wish/desire” in the Tatar language as a functional-semantic field of desire is perspective.